2014
DOI: 10.1186/1477-7819-12-338
|View full text |Cite
|
Sign up to set email alerts
|

An uncommon long-term survival case of primary cardiac leiomyosarcoma

Abstract: Primary cardiac sarcoma is a rare aggressive entity. It constitutes the second most common type of primary cardiac neoplasms. Its management has largely been guided by small retrospective series with a median survival of 6 months. Here, we discuss a unique case of 8-year survival cardiac leiomyosarcoma managed by surgical and adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Despite having a large tumor with pathologically poor prognostic features, our patient is doing well 9 years after therapy. With 2 patients with 7 and 8 years [6] of survival recently reported in the literature, and our patient's 9-year survival, we suggest that long-term survival following treatment for primary cardiac leiomyosarcoma…”
Section: Commentsupporting
confidence: 62%
“…Despite having a large tumor with pathologically poor prognostic features, our patient is doing well 9 years after therapy. With 2 patients with 7 and 8 years [6] of survival recently reported in the literature, and our patient's 9-year survival, we suggest that long-term survival following treatment for primary cardiac leiomyosarcoma…”
Section: Commentsupporting
confidence: 62%
“…Table shows similar cases that survived for over 24 months with the available data regarding treatment modalities and outcome ( 12 - 28 ). A long survival was reported 17 cases.…”
Section: Discussionmentioning
confidence: 80%
“…Although most patients die within 1 year of diagnosis, Glaoui et al have reported an 8-year survival duration after combined surgical and adjuvant radiochemotherapy. [4] While echocardiography is currently a widely-used method for diagnosing cardiac masses, differential diagnosis of cardiac tumors often presents a challenge for the sonographer. When malignancy is suspected, MRI and CT remain essential for operative planning and identification of tumor extension.…”
Section: Discussionmentioning
confidence: 99%